Bridging the Implementation Gap: Addressing Academic and Structural Barriers to Injury Prevention in University-Level Contact Sports - Haithem Nasr; Hassan Abdelnour; Meftah Madi; Mastoura Aksh (The Indonesian Institute of Science and Technology Research, 2026)
Sports injuries, particularly musculoskeletal injuries, are common among athletes and affect more than 40% of active individuals annually. University athletes are especially vulnerable during training and competition, particularly in contact sports such as football. Although evidence-based prevention strategies, including neuromuscular training and appropriate warm-up and cool-down routines, can significantly reduce injury risk, their implementation remains inconsistent in many university settings. This study aimed to evaluate the knowledge and adoption of injury prevention strategies among student-athletes at the University of the Western Cape (UWC) and identify barriers affecting their implementation. A descriptive study design was employed involving 101 student-athletes selected through purposeful and convenience sampling. Data were collected using validated questionnaires addressing sociodemographic characteristics and preventive practices. Data analysis was conducted using SPSS version 24. The findings revealed that most participants were aged 20–24 years and had 1–2 years of sporting experience. Football was identified as the most common sport among respondents. Doctors, physiotherapists, and coaches were recognized as the primary sources of injury prevention knowledge. However, the practical application of preventive measures was limited by structural and academic barriers. Many athletes reported skipping warm-up activities due to a lack of time and neglecting cool-down exercises because of exhaustion. The study concludes that despite adequate theoretical knowledge, injury prevention practices among student-athletes remain insufficient. Universities should implement mandatory and integrated safety protocols within training schedules to improve athlete safety and long-term performance.